Web-Based Survey for Consumers - M Iffan; N Shafira (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this study is to describe the advantages of Web-based survey for Users as Consumers. The method used in this study was a qualitative method in which the data presented are data from phenomena. The results of this study proved that Web-based survey had advantages to the users as consumers viewed through how the survey team gave rewards to users after finishing surveys, the features of the web and users would help the companies by their surveys. The conclusion obtained in this study is relationships between other companies, survey teams and users as consumers have benefit to each other.